Internet Shutdown with Violations of Human Rights and Freedom of Speech - Hussain, Remsha; Kabir, Russell; Kar, Sujita Kumar; Arafat, SM Yasir (Asian Journal of Public Health and Nursing, 2024)
In the current time the world is too connected with the virtue of internet. Health systems around the world are become more digitalized and dependent on internet connectivity for their operations, making them and their beneficiaries more susceptible to the effects of outages. Internet ensures the basic human rights like freedom of expression and internet shutdown hampers the progression to the sustainable development goals (SDGs; Myanmar, 2019). Recently, Bangladesh has experienced a mass uprising with a demand of quota reformation for entering the public services. There were at least 757 killings, hundreds were injured, and thousands were arrested (Hasan, 2024). During the protest, the internet was shut down by the Bangladeshi government on July 18–23 and August 4–5, severely curtailing the country's citizens' ability to express themselves freely and gather in peace (UN Human rights, 2024). The country has also experienced sheer violations of human rights (Human Rights Watch, 2021). These shutdowns, which prevented users from accessing social media sites like Facebook and Twitter, hindered information sharing, reduced public scrutiny of law enforcement, and increased the likelihood of impunity. The situation was made worse by threats against journalists. That internet shutdown fear, apprehension, disconnected with the friends and family members. It also hindered the tele-medicine and other internet-based services. The limitations on one's freedom of movement also made it much harder to do business, go about daily life, and obtain necessities. Due to political instability, hospital overcrowding, some injured protesters were unable to get timely medical attention. The disturbance has had a substantial impact on the economy as well, particularly on companies and transportation. Curfews and shutdowns exacerbated the already poor economic situation by impeding not just the emergency response but also the supply chain for basic products and services (Figure 1). The right to education was negatively harmed by the closing of colleges and universities, and children's wellbeing was generally impacted (UN Human rights, 2024). In July 2023, following the unexpected arrest of Pakistan Tehreek-e-Insaf (PTI) leader Imran Khan, a wave of unprecedented Internet blocking swept across the country, forcing millions of Pakistanis into digital isolation. The country's online connectivity abruptly stopped working for three days, severely affecting many different economic sectors and upsetting the lives of countless people who rely on the Internet for their livelihoods. Individuals who worked from home or remotely discovered that they were unable to complete their work assignments, and social media content producers found it difficult to maintain relationships with their followers. The abrupt unavailability of online health services, which are essential for remote consultations and medical help, has raised concerns about the safety of numerous individuals. Even necessities like biometric systems and ATMs malfunctioned, adding to the public's confusion and hardship (Tahir and Salim, 2023). In August, 2024, Internet was slowed again in Pakistan. The incident is a part of a larger government drive to quell dissent, especially directed at followers of former prime minister Imran Khan, whose political campaigns have benefited greatly from his use of social media (Rehman and Goldbaum, 2024). In Kashmir, India Internet was blocked all mobile and broadband internet access in the area in August 2019 (India Press Trust, 2020). This internet access hindered the access to vital health information during the times of Covid-19. The capacity to download important information, access telemedicine, or conduct online consultations were severely constrained, where healthcare workers battled with slow 2G internet. These further strains the already overburdened healthcare system (Shoib and Arafat, 2020). Internet shutdown was also noted in West Bengal in 2022. Internet shutdown has also been noted in Myanmar (Myanmar, 2019). Between 2016 and 2021, the #KeepItOn group documented 931 Internet shutdowns in 74 countries, primarily in Africa and South Asia, with 12 of those nations implementing more than ten shutdowns (Figure 2, Accessnow, 2024). These measures represent a novel and growing threat to several aspects of global public health, human rights, and freedom of expression. Authorities have shut down the internet completely during times of political instability, civil disobedience, or perceived risks to national security, leaving millions of people without access. These actions, which are frequently explained as required to keep the peace, have made things worse by escalating human misery, limiting free speech, and isolating communities. As the internet becoming an essential tool for healthcare delivery, outages are becoming more dangerous for people's lives. Although there is a dearth of empirical research to quantify the effects, anecdotal evidence indicates that blanket blackouts can disrupt essential communication channels between patients and physicians (telemedicine), cause shortages of medications for chronic diseases, postpone the deployment of vital medical personnel to emergencies, and jeopardize the financial stability of healthcare providers (Rydzak 2018). These problems were brought to light by the Covid-19 pandemic: some communities in Myanmar were unaware of the virus's existence months into the pandemic due to blackouts that cut off entire regions from life-saving public health advice. In Kashmir, shutdowns hindered the download of mobile test and trace apps, impeding efforts to contain the virus as infection rates surged throughout the subcontinent (Parvaiz, 2020). Patient lives rely heavily on online health services. Internet access is essential to many hospital operations, procedures, and patient medical record access. Long-term internet outages can also render vital medical equipment antiquated and possibly unusable. The delivery of healthcare may be significantly impacted by this, especially in areas with little resources. Internet outages have occasionally impacted entire nations, although they often target a specific population or geographic area to restrict the free flow of information there. Usually, they are used to cover up flagrant violations of human rights (OHCHR, 2022). Internet shutdowns not only limit freedom of expression, but they also violate human rights, negatively hurting the population's well-being. People who are disconnected are deprived of access to basic services, which has an impact on all facets of life, including employment, education, health care, and financial security, particularly for freelancers. These closures restrict free speech, obstruct journalism, and make it more difficult to record violations of human rights. They also make it impossible for people to obtain information that could save lives during emergencies and conflicts (Access Now, 2023) A multifaceted approach is needed to address internet restrictions, including legal frameworks to defend digital rights, international pressure to drive policy reforms, and lobbying and awareness raising to highlight the implications on human rights. United Nations urged for internet resumption in Myanmar (Myanmar, 2019). Kolkata High court intervened Internet shutdown in West Bengal, India (Bapat and Mishra, 2022). While users should educate themselves on how to be ready for a shutdown and use technological tools like decentralised networks and VPNs to get around internet restrictions, civil society should also take the lead in providing emergency solutions. It is imperative to actively take action to defend your rights and freedom of expression, particularly in the face of attempts by powerful political entities to suppress them. In conclusion, the advent of internet shutdowns can be attributed to the growing significance of the digital world in achieving numerous human rights. Turning off the Internet has irreversible negative effects on material and human rights terms. Governments restrict internet access in the name of national security, public order, stopping the spread of misinformation, or public safety. These defenses, nevertheless, are usually criticized for being employed to stifle criticism, restrict free speech, and hide violations of human rights. It causes enormous problems including health and well-being.